THE EFFECTIVE THERMAL CONDUCTIVITY OF POROUS GLASSES SATURATED WITH FLUIDS - G. G. Guseinov (Вестник Дагестанского государственного технического университета: Технические науки)
Effective thermal conductivity of the porous glasses saturated with the carbon dioxide, n – hexane, and oil has been researcher in the temperature intervals from 290 K to 380 K and at the pressures from 1.333Pa to 18.7 MPa.Heat passage mechanisms has been detected, the influence of temperature and pressure has been studies, the effect of CO2, C6H14, and oil molecules, being inside pores, on the behaviour of effective thermal conductivity of porous glasses. Heat passage mechanisms in the porous mediasaturated by fluid has been detected.